Birth Asphyxia - Clinical Experience and Immediate Outcomes - Arshad Rafique , Muhammad Akram , Rizwan Asad Khan, Muhammad Fakhar-ul-Zaman, (Journal of Rawalpindi Medical College, 2017)
To find out immediate outcome of neonates with birth asphyxia and its association with risk factors. Methods: This cross sectional study included all consecutive babies admitted with diagnosis of birth asphyxia . Babies with congenital heart disease, congenital malformations and prematurity were excluded. Biodata and clinical parameters including place of delivery,dai handling,time of arrival in hospital,mode of delivery, grades of hypoxic ischemic encephalopathy, outcome in terms of discharge and death were recorded. Results: Sixty one patients were included in the study. Majority (80.3%) were male..Mothers having regular antenatal checkup were 65.5%. Eleven (18%) babies were home delivered and 50(82%) in hospital setup. In 16.4% babies there was history of dai handling. 60.7% babies were delivered by SVD and 39.3 % by C- section. Majority (83.6 %) presented within 6 hours. Hypoxic ischemic encephalopathy stage I, II and III was seen in 39.3%, 49% and11.5% respectively. Forty eight (78.7%) babies were discharged and 13(21.3%) died. No evidence of association was found between outcome at discharge and time of arrival at hospital (p value=0.33)and dai handling (p value= 0.114). Significant association was found between outcome at discharge and place of delivery (p value=0 .031) and outcome at discharge and hypoxic ischemic encephalopathy stage (p value=0.000). Conclusion: Asphyxiated newborns have significant short term mortality in association with home deliveries and hypoxic ischemic encephalopathy stage III